A Prototype Software System for Intra-procedural Staff Dose Monitoring and Virtual Reality Training for Fluoroscopically Guided Interventional Procedures. - Troville, Jonathan; Rudin, Stephen; Bednarek, Daniel R. (Journal of Digital Imaging, 2023)
Staff dose management in fluoroscopically guided interventional procedures is a continuing problem. The scattered radiation display system (SDS), which our group has developed, provides in-room visual feedback of scatter dose to staff members during fluoroscopically guided interventional (FGI) procedures as well as extra-procedure staff and resident training. There have been a number of virtual safety training systems developed that provide detailed feedback for staff, but utilize expensive graphics processing units (GPUs) and dosimeter systems, or interaction with the x-ray system in a manner which entails additional radiation exposure and is not compatible with the As Low as Reasonably Achievable paradigm. The SDS, on the other hand, incorporates a library of look-up-table (LUT) room scatter distributions determined using the EGSnrc Monte Carlo software, which facilitates accurate and rapid system update without the need for GPUs. Real-time display of these distributions is provided for feedback to staff during a procedure. After a procedure is completed, machine parameter and staff position log files are stored, retaining all of the exposure and geometric information for future review. A graphic user interface (GUI) in Unity3D enables procedure playback and interactive virtual-reality (VR) staff and resident training with virtual control of exposure conditions using an Oculus headset and controller. Improved staff and resident awareness using this system should lead to increased safety and reduced occupational dose.